Pelatihan Bahasa Inggris Berekuivalen Toefl terhadap Mahasiswa Universitas Muhammadiyah Palangkaraya - Suniati Suniati; A’am Rifaldi Khunaifi; Dedy Setiawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Community service aims to provide not only knowledge but also the readiness to face the TOEFL exam required as a condition of graduation for students of Muhammadiyah University of Palangkaraya. Community service is carried on in a university environment in six meetings for three weeks, the target communities are communities such as students of Muhammadiyah University. The method used in this service is to provide training to students. Cost of service activities is entirely sourced from Muhammadiyah University of Palangkaraya from APBU Year 2015. After the implementation of English training activities, the students have sufficient readiness to take the TOEFL test became a graduation requirement for students of Muhammadiyah University of Palangkaraya .